Clinical codes combined with procedure codes increase diagnostic accuracy of Crohn’s disease in a US military health record - Susan Hutfless; Manish Singla; Elie Al Kazzi; Benjamin Rodriguez; John Betteridge; Steven R Brant (BMJ Open Gastroenterology)
Background and aims Previous examinations of International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) codes to predict accuracy of diagnosis in inflammatory bowel disease have had limited chart review to confirm diagnosis. We aimed to evaluate using the ICD-9-CM for identifying Crohn’s disease (CD) in a large electronic health record (EHR) database.Methods This is a retrospective case-control study with a 3:1 allocation of EHRs of active duty service members diagnosed with CD from 1996 to 2012. Subjects were selected by having two ICD-9-CM codes for CD and none for ulcerative colitis during the study period. Gastroenterologists reviewed each chart and confirmed the diagnosis of CD by analysing medication history and clinical, endoscopic, histological, and radiographic exams.Results 300 cases of CD were selected; 14 cases were discarded due to lack of data, limiting analysis to 284 subjects. Two diagnostic codes for CD had sensitivity and specificity of 1.0 and 0.53 respectively, for confirmed CD. If two or more encounters listing CD were with a gastroenterologist, the sensitivity and specificity was 0.71 and 0.87 respectively. If two encounters included a colonoscopy was performed at the same time as a CD code, sensitivity and specificity was 0.49 and 0.88 respectively.Conclusions The relatively poor specificity of ICD-9-CM codes in making the diagnosis of CD should be taken into consideration when interpreting results and when conducting research using such codes. Limiting these codes to patients given this diagnosis by a gastroenterologist, or to those who had a colonoscopy at the time of a diagnosis, increases the specificity, although at cost of sensitivity, especially for colonoscopy.